OVERT HYPOTHYROIDISM COMPLICATED BY STROKE IN A YOUNG PREGNANT WOMAN - Hairani, Noor Amirah Mohd; Ng, Ooi Chuan; Bahrudin, Mohd Fyzal (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Overt hypothyroidism in pregnancy presenting with stroke is infrequent. Physiological changes during pregnancy have the potential of masking hypothyroidism, making its diagnosis challenging. Hypothyroidism in pregnancy augments the hypercoagulable state leading to stroke. CASE We are reporting a previously well 25-year-old female, who was gravida 2 para 1 at 9 weeks of gestation who presented with sudden onset of right sided body weakness, slurring of speech and headache. She was found to have overt hypothyroidism. She had weight gain of 8 kg for 2 months associated with constipation. At presentation, she had a brief loss of consciousness followed by slurred speech and numbness over the right limb. Her GCS was E4V5M6 with blood pressure of 144/96 mmHg, regular pulse rate of 80 beats per minute and normal temperature. She has no goitre, coarse hair, and pitting oedema. National Institutes of Health (NIH) stroke scale was 9/42. MRI revealed left basal ganglia infarct with large vessel occlusion at M1, while the cerebral angiogram shown left M1 occlusion. As thrombolysis was contraindicated because of pregnancy, thrombectomy was attempted. Left M1 occlusion was recanalized but residual clot persisted at superior branch of left M1. Autoimmune work-up was negative. Additional laboratory work-up for young stroke, revealed significantly abnormal thyroid function tests with T4: 7 pmol/L (9-19 pmol/L) and TSH of 14.87 mIU/L (normal value: 0.35-4.94 mIU/L). With positive antithyroglobulin (TG) antibodies of 1189.4 IU/mL (normal value: <4.11 IU/ml) and anti- thyroperoxidase (TPO) antibodies of 1158.4 IU/ml (normal value: <5.61 IU/ml), a diagnosis of hypothyroidism secondary to Hashimoto’s disease was made. She was given thyroxine replacement. Conclusion In conclusion, overt hypothyroidism in pregnancy is associated with an increased risk of stroke due to changes in lipid metabolism, inflammation, and blood coagulation. Pregnant women with hypothyroidism should receive appropriate management to reduce their risk of stroke.